The effectiveness of the KIANO (knees in, angkles out) position in the second stage of labor to reduce perineal tear - Ari Andriyani; Anugrah Destya Trisetyanigsih; Mahindria Vici Virahaju; Eva Nurul Fianty; Pipit Haryati; Emi Narimawati; Galih Puspita Sari; Kornelia Putri; Adud Adud (Science Midwifery, 2025)
The WHO estimates that perineal trauma rates are approximately 85% in vaginal deliveries, and most cases require perineal repair. Efforts to minimize the risk of perineum tear involve performing antenatal perineal massage alongside the use of warm perineal compresses during the second stage of childbirth, as well as various alternative birthing positions other than lithotomy. Conventional birthing positions, such as with the knees apart and feet parallel, are often unhelpful. Ideally, biomechanically during the second stage, the birthing position should optimize the diameter of the pelvic inlet to facilitate descent of the baby's head, such as with the knees together and the heels apart, which allows for sacral nutation and widening of the pelvic outlet. This study aims to determine the effectiveness of the KIANO (knees in, ankles out) maneuver in mothers in the second stage of labor in reducing perineal tears. A true experimental method with a post-test control group design was applied in this study. It was conducted at the Jetis and Tegalreo Community Health Centers, Tutik Purwani and Emi Narimawati TPMB, from July to October 2025. The subjects were primiparous women in their second stage of labor who met inclusion and exclusion criteria. The sampling technique used simple random sampling, with 60 women divided into two groups: 30 primiparous women with the KIANO intervention and 30 primiparous women as the control group.  Statistical analysis was performed with JASP version 0.19.1.0. Due to non-normal data distribution, Mann–Whitney U test was selected. The findings revealed a significant difference in degree of perineal tearing between intervention and control groups, demonstrating a small to moderate effect size (r = –0.240). It can be concluded that the KIANO method is effective in reducing the degree of perineal tearing during labor compared to the conventional method.